2013
DOI: 10.1371/journal.pone.0071272
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Mediated Gene Silencing of Nicotinamide N-Methyltransferase Is Associated with Decreased Tumorigenicity in Human Oral Carcinoma Cells

Abstract: Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer. Despite progress in the treatment of OSCC, overall survival has not improved substantially in the last three decades. Therefore, identification of reliable biomarkers becomes essential to develop effective anti-cancer therapy. In this study, we focused on the enzyme Nicotinamide N-methyltransferase (NNMT), which plays a fundamental role in the biotransformation of many xenobiotics. Although several tumors have been associated with abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 43 publications
(60 reference statements)
3
47
0
Order By: Relevance
“…Although several cancers have been associated with abnormal NNMT expression, its role in cancer cell metabolism remains largely unknown. We previously demonstrated that downregulation of NNMT expression in human oral and lung cancer cell lines significantly inhibited cell growth and tumorigenicity, suggesting that NNMT could play a critical role in the proliferation and tumorigenic capacity of cancer cells, and the possibility of NNMT as a therapeutic target for the treatment of tumor [62][63][64]. In this work, since CSCs appear to be responsible for tumor initiation and progression (for tumor onset, self-renewal/ maintenance, and metastasis), we decided to analyze the mRNA expression and catalytic activity of NNMT in CSCs enriched populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although several cancers have been associated with abnormal NNMT expression, its role in cancer cell metabolism remains largely unknown. We previously demonstrated that downregulation of NNMT expression in human oral and lung cancer cell lines significantly inhibited cell growth and tumorigenicity, suggesting that NNMT could play a critical role in the proliferation and tumorigenic capacity of cancer cells, and the possibility of NNMT as a therapeutic target for the treatment of tumor [62][63][64]. In this work, since CSCs appear to be responsible for tumor initiation and progression (for tumor onset, self-renewal/ maintenance, and metastasis), we decided to analyze the mRNA expression and catalytic activity of NNMT in CSCs enriched populations.…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC-UV method used for the determination of NNMT activity was based on the method developed by Valentina Pozzi et al [13]. The cell pellet (5 Â 10 6 cells) samples were prepared by homogenization in 200 ll of cold lysis buffer as previously described followed by centrifugation at 16,000g for 10 min at 4°C.…”
Section: Nnmt Enzyme Assaymentioning
confidence: 99%
“…One hundred microliters of the neutralized supernatant was injected into a high-performance liquid chromatography system with a Hewlett-Packard 1100 photodiode array detector (Waldbronn, Germany) using a 250 Â 4.6-mm-inner-diameter Agilent TC-C18 5-lm reversed-phase column. The chromatographic analysis of the extracted supernatant was performed as previously described [13]. The peak areas corresponding to 1-MNA were integrated, and the enzyme activities were tested by measuring the amount of 1-methylnicotinamide (1-MNA) produced.…”
Section: Nnmt Enzyme Assaymentioning
confidence: 99%
“…It has been reported that the NNMT expression is related with differentiation of oral cancer cells and may be a biomarker for OSCC treatment (Emanuelli et al, 2010). A recent study revealed that the abnormal expression of NNMT was closely associated with the metabolism of oral squamous carcinoma cells (Pozzi et al, 2013). The decreased expression of NNMT was able to suppress cancer cell proliferation and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased expression of NNMT was able to suppress cancer cell proliferation and tumor development. The inhibition of NNMT showed potential capacity for oral cancer treatment by molecular approach (Pozzi et al, 2013). Besides, MMP9 (Matrix Metalloproteinases-9) is reported to be significantly activated in malignant tissues of patients with oral cancer (Patel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%